INCREASING TREND OF NITRATE CONTAMINATION OF TEHRAN SOUTHWEST GROUNDWATER AQUIFER OF IRAN - K. Imandel; A.A. Farshad; L. Mir-abdollah (Tehran University of Medical Sciences, 2000)
To assess the pollution trend of southwest ground water aquifer of Tehran by nitrite and nitrate, in February 1999, out of 300 wells within this area, 99 wells were selected according to simple random sampling without replacement, analysed by colorimetric and ultraviolet spectrophotometric screening standard methods, respectively. The conclusion asserted is that with a confidence limit of 95%, standard error of 2, and permissible error of ± 2.21, the average concentration of nitrate in southwest Tehran ground water aquifer is 48 to 56 mg/l as No-3. Comparison the results of this survey with the data collected in 1993, it was concluded that the nitrate concentration in aquifer has increased 2.4 fold whereas the nitrite has reduced about 4 fold. One of the reasons for these changes is the process of denitrification occurred under the recently made hydrochemical conditions of layers, and finally there was a significant decrease in No-3 levels with depth. Concentration appraisal of the sum of the ratio of the concentration of each parameter (nitrate & nitrite) to its respective guide line value showed that 52.5 percent of wells under the study exceed the number one recommended guide line and health significance in drinking water by W.H.O.